2014
DOI: 10.1016/j.bbmt.2014.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of BK Polyoma Virus (BKV) in the Urine with Hemorrhagic Cystitis and Renal Function in Recipients of T Cell–Depleted Peripheral Blood and Cord Blood Stem Cell Transplantations

Abstract: Hematopoietic stem cell transplant (HSCT) recipients are at significant risk for BKV reactivation, hemorrhagic cystitis (HC) and renal dysfunction. We prospectively monitored 98 HSCT by serial BKV PCR in the urine through Day (D) +100 to analyze the relationship between BKV viruria and HC, serum creatinine (Cr) and creatinine clearance (CrCl) through D +180 or death. Patients, median age 52 years, range 20-73, received T-cell depleted (50%) or cord blood allografts (21%). Median pre-HSCT BKV IgG titers were 1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 32 publications
8
21
0
Order By: Relevance
“…Finally, Lee et al measured BKV antibodies in 98 adults undergoing HCT and reported that increasing titers were associated with viruria. Using the same assay as our analysis and similar to our findings, all 98 subjects (100%) had a detectable BKV IgG of >1:640 [19]. …”
Section: Discussionsupporting
confidence: 84%
“…Finally, Lee et al measured BKV antibodies in 98 adults undergoing HCT and reported that increasing titers were associated with viruria. Using the same assay as our analysis and similar to our findings, all 98 subjects (100%) had a detectable BKV IgG of >1:640 [19]. …”
Section: Discussionsupporting
confidence: 84%
“…Several risk factors alone or in association with BKPyV have been reported to contribute to the development of HC, including GVHD, chemotherapeutics and supportive medications, and other bacterial or viral infections . In the present study, patients affected by HC showed a higher incidence of CMV reactivations (>1000 IU/mL), which has been previously correlated with BKPyV‐associated HC .…”
Section: Discussionsupporting
confidence: 79%
“…Fittingly, patients detected to be BKPyV positive in urine only did not develop clinical relevant HC. 15,30,[32][33][34][35][36] In the present study, patients affected by HC showed a higher incidence of CMV reactivations (>1000 IU/mL), which has been previously correlated with BKPyV-associated HC. 15 In line with the more protracted course of higher-grade HC (above) in conjunction with lymphocyte recovery and GVHD, patients with HC of grade II/III developed significantly more often GVHD after day+100 than those with low-grade HC.…”
Section: Discussionsupporting
confidence: 60%
“…Hemorrhagic cystitis (HC) is a severe complication in patients undergoing hematopoietic stem cell transplantation (HSCT), resulting in significant morbidity, such as nephropathy and renal failure, prolonged hospitalization, and prolonged blood transfusion requirement [1,2]. Effects on mortality have also been reported in children undergoing HSCT [3].…”
Section: Introductionmentioning
confidence: 99%